Life path, main periods and scientific activity directions of A.A. Bogomolets - Sharlai, N. (Problems of Engineer-Pedagogical Education, 2021)
The leading aspects of scientific - pedagogical activity of Alexander Alexandrovich Bogomolets of medical science development are covered in the article. The purpose of the article is the scientific - organizational and pedagogical activities of Alexander Bogomolets. The problem solution is achieved by solving the following following tasks: to analyze historical - pedagogical and scientific literature, as well as publications in periodicals of XIX - XX centuries, to determine progressive and traditional approaches, practical experience, pedagogical heritage of the past. As a result of the historical analysis, a biographical sketch of the life and professional activity of the outstanding scientist Alexander Alexandrovich Bogomolets is described, chronological periods of professional activity are determined. The contribution of Alexander Bogomolets to the development of teaching activities and the factors of forming the ideas of professional medical education in the scientific and pedagogical heritage are substantiated. Analyzing the experience of educators, namely: V. Sukhomlinsky, and Makarenko, Y. Dzerovich, A. Voloshin, G. Vashchenko, and А.Zhivotka, V. Barvinsky, Y. Kuzmiv, A. Krushelnitsky, I. Ogienko, S. Syropolka, and others ., scientists ought to determine the ways of further development and prospects for improving education and upbringing. In recent years, scientists have been considering studies of pedagogical personalities at a new level, analyzing them in the aggregate of the system of personal, social and internally scientific determinants. Scientists of modern Ukraine basically justify the educators according to Specific criteria: teachers on the same vital Way and professional pedagogical moto; educators who worked in the paradigm of national pedagogy; Bright scientists that led cultural and educational societies, pedagogical organizations, etc. At the same time, the pedagogical heritage of prominent scientists that small scientific schools in the entire former Soviet Union and bliskuchii were invested in the formation of scientific national elites in the XX century, when the process of higher education system development took place on Ukrainian lands, the struggle between the communist and national ideas intensified, when the concept of nation (national consciousness) and the concept of “Soviet man” were put forward, active educational work took place, etc., remained insufficiently studied that violates the integrity of the domestic history of education.